PENGEMBANGAN INDUSTRI BATIK RIAU PADA RUMAH KREATIF CEMPAKA DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Dede Widiasti; Wahyu Hamidi; Jahrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was aimed to find out the Strengths, Weaknesses, Opportunities and Threats in Riau Batik Industry of Rumah Kreatif Cempaka at subdistric of Rumbai Pesisi of Pekanbaru and to formulate the suitable strategy to develop the industry Thisresearch was a descriptive research. It had primary and secondary data that were analyzed using SWOT analysis method. SWOT analysis method is a strategic planning method used to evaluate Strengths, Weaknesses, Opportunities, and Threats involved in one project.Based on the SWOT analysis, it was found out the internal factors that influence the development of the industry were; It had unique products and high competitiveness as main Strength with 1,74 score. The main weakness was the insufficiency of the raw materials which reached score up to 1,1. The external factors were Opportunities and Threats. The main opportunities factor in this industry was the existence of regulation and policy from the government about the development of creative industry which reach score up to 1,67. Meanwhile the main Threats factor of the Industry was the excessive similar products with different materials in the market which reached sore up to 1,1. Based on the IFAS table, the difference between the Strengths factor and Weaknesses factor was 0,64 and from EFAS table the difference of Opportunities and Threats factor was 0,57. Therefore SWOT analysis could be made, it could be found out that the position of Rumah Kreatif Cempaka is in Cell-1 which meant the Aggressive Strategy was more focus on Strengths Opportunities Strategy (SO).Keywords: Riau Batik Industry, Development, Rumah Kreatif Cempaka and SWOT.